2021
DOI: 10.1038/s41418-021-00858-0
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 controls the lineage fates of BMSCs during skeletal aging by impairing mitochondrial function and pluripotency maintenance

Abstract: Aged bone marrow mesenchymal stem cells (BMSCs) exhibit aberrant self-renewal and lineage specification, which contribute to imbalanced bone-fat and progressive bone loss. In addition to known master regulators of lineage commitment, it is crucial to identify pivotal switches governing the specific differentiation fate of aged BMSCs. Here, we profiled differences in epigenetic regulation between adipogenesis and osteogenesis and identified super-enhancer associated lncRNA nuclear-enriched abundant transcript 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…Nuclear-abundant lncRNAs NEAT1 and MALAT1 are shown to localize to hundreds of genomic sites in human cells, preferentially to active genes ( West et al, 2014 ). NEAT1 regulates aberrant self-renewal of bone marrow mesenchymal stem cell lineage during skeletal aging by mediating mitochondrial function ( Zhang et al, 2022 ). Whereas, in vascular endothelial cells SIRT6-mediated suppression of MALAT1 resulted in aging-induced endothelial to mesenchymal transition through Snail upregulation ( Qin et al, 2019 ).…”
Section: Genome Integrity and Senescencementioning
confidence: 99%
“…Nuclear-abundant lncRNAs NEAT1 and MALAT1 are shown to localize to hundreds of genomic sites in human cells, preferentially to active genes ( West et al, 2014 ). NEAT1 regulates aberrant self-renewal of bone marrow mesenchymal stem cell lineage during skeletal aging by mediating mitochondrial function ( Zhang et al, 2022 ). Whereas, in vascular endothelial cells SIRT6-mediated suppression of MALAT1 resulted in aging-induced endothelial to mesenchymal transition through Snail upregulation ( Qin et al, 2019 ).…”
Section: Genome Integrity and Senescencementioning
confidence: 99%
“…A previous study has implied that NEAT1 is upregulated in aged bone marrow mesenchymal stem cells (BMSCs) and regulates mitochondrial function by sponging miR-27b-3p. 41 Additionally, NEAT1 is a marker of COPD susceptibility, and NEAT1/miR-193a affects the development of COPD. 42 In CSE-exposed 16HBE cells, XIST/miR-200c-3p/EGR3 can intensify inflammation action and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adipogenesis and adipose deposition are regulated by post-transcriptional factors, such as noncoding RNAs (ncRNAs) . Zhang et al identified transcriptional and epigenetic regulatory differences between adipogenesis and osteogenesis and identified NEAT1, a long ncRNA (lncRNA) associated with super-enhancers (SEs), as a key molecule in the differentiation of bone marrow stromal cells . Several studies have identified several ncRNAs that affect adipogenesis and adipose deposition during the various regulatory stages of adipocyte proliferation and differentiation. , …”
Section: Introductionmentioning
confidence: 99%
“…8 Zhang et al identified transcriptional and epigenetic regulatory differences between adipogenesis and osteogenesis and identified NEAT1, a long ncRNA (lncRNA) associated with super-enhancers (SEs), as a key molecule in the differentiation of bone marrow stromal cells. 9 Several studies have identified several ncRNAs that affect adipogenesis and adipose deposition during the various regulatory stages of adipocyte proliferation and differentiation. 10,11 Circular RNAs (circRNAs) are among the most valuable and important ncRNAs, referring to RNA molecules with a circular structure covalently linked at the 3′ and 5′ ends, constituting a recently discovered, widespread and abundant class of RNAs.…”
Section: ■ Introductionmentioning
confidence: 99%